Inspirations the world's most beautiful embroidery - Bauer, Margie (south australia : Margie Bauer, 2004)
elegant cushion with delicate roses - cosy blanket for beginners - .
caprice / gentle touch / hidden treasure / la vie rose / debut / winter love.
All age.
Keywords: industrial art and design; Embroidery .